Development of the E2A2E Learning Model with a SOLO Taxonomy-based Deep Learning Approach to Improve The Moral Character of Madrasah Aliyah Students - Manshur, Ahmad; Anisah, Giati; Ahmad, Mas Tajjudin (Fakultas Tarbiyah - Universitas Nahdlatul Ulama Sunan Giri, 2025)
Moral education in Islamic high schools often only addresses cognitive aspects without practical implementation, thus requiring a learning model that encourages the internalization of moral values. This study aims to develop the E2A2E (Engage, Explore, Analyze, Apply, Evaluate) learning model using a deep learning approach based on the SOLO taxonomy to improve students' moral character. The research method uses the ASSURE development model through the stages of analysis, design, implementation, and evaluation. The results show that the E2A2E model is highly feasible (average feasibility >88%) with a significant increase in students' understanding from the unistructural to the extended abstract level. In conclusion, this model is efficacious in improving students' moral awareness and ethical behavior. For further research, it is recommended to test this model in a broader context and integrate digital technology to optimize results.